Online Listening Comprehension Learning Problems of Semester I and III Students at Academy of Foreign Language Balikpapan - Era Wahyu Ningsih; Suzanna Widjajanti (Acitya: Journal of Teaching and Education, 2022)
This research was conducted to find out the problems encountered in online Listening comprehension lectures during the student pandemic at the Balikpapan Foreign Language Academy semester I and III and to find out the methods used by students in overcoming the problems they faced, this field research was conducted at the Balikpapan Foreign Language Academy, with the research subjects being all first and third semester students who have attended Listening Comprehension lectures for approximately one semester. This study used descriptive qualitative methods with data collection using observation, literature review and interviews involving first and third semester students consisting of 25 students, 6 male students and 19 female students. The collecting data using observation, literature review and interviews as a complement to the required data, from all data collection activities it was concluded that students who took part in lecture activities at the Balikpapan Foreign Language Academy in the listening comprehension course had all studied English with 3 months to With 15 years, ABA Balikpapan students have experience problems in the online learning process, especially listening comprehension courses, including unsupported internet networks, audio that cannot be heard clearly, noise from the environment around the lecturer or the students themselves, interference from devices that sometimes error and often forget the existing tasks. This study lasted approximately 4 (four) months, starting from data collection to writing research reports and from the results of this study. The implication of the study for teacher of Listening Comprehension, all the problems mentioned in this study should be identified and should be minimized prior to conducting the class to gain maximum output, for the students, they need to have a free audio disturbance environment when attending the listening comprehension class online.